MENINGITIS - CAUSES, SYMPTOMS, AND MODERN TREATMENT METHODS - Tolmasov Ruzibek Tolmasovich; Robiya Akbarova; Abduxoshimova Sevinch (Web of Journals Publishing, 2025)
Meningitis is an acute inflammation of the meninges, the protective membranes covering the brain and spinal cord. The disease can be caused by various infectious agents such as bacteria, viruses, fungi, or parasites, and, in rare cases, by non-infectious factors including certain medications and autoimmune reactions. Meningitis remains a global health concern due to its rapid progression, high mortality rate, and risk of long-term neurological complications. This paper discusses the etiology, clinical manifestations, diagnostic methods, and contemporary approaches to the treatment of meningitis. Special attention is given to the advances in antimicrobial therapy, immunization strategies, and supportive care techniques that have significantly improved patient outcomes in recent years.
Keywords: Meningitis, inflammation, central nervous system, bacterial infection, viral infection, diagnosis, antibiotic therapy, vaccination, prevention.